Analysis of use of virtual spaces in higher education - Édgar Alfonso Pérez García; José de Jesús Rodríguez Sánchez (Universidad de Guadalajara, 2022)
This work aims to know how the trend in the use of virtual spaces is, from the proposals is of incorporating technology in the teaching practice in Higher Education and knows if the level of use of information and communication technologies (ICT) affects the design and development of the proposals. In this work was used a correlative transactional methodology and the process was concurrent by complementation with a group of professors from a Mexican public university. We observed that sending and receiving documents is the most used dynamic and that, the main obstacles and difficulties are get internet accessibility and the connection speeds. The main learning activity used is creating individual documents. We concluded that, the level of skill in use of ICT that the teacher considers having does not improve the integration of technologies inside of teaching practice, and that the use of virtual spaces is oriented towards instrumental aspects (do not spent paper, automatic evaluation, and others), the possibility of structuring pedagogical proposals with integration of ICT that seek to improve the teaching and learning process in students is left aside.